Personal epistemology and learning in a chemistry classroom - Pulmones, Richard (2013)
This paper reports a qualitative investigation of student's epistemological beliefs in science and in Chemistry and of how such epistemology is linked with their metacognitive behaviors. Epistemological beliefs are conceptualized as being made up of independent dimensions activated in context and operating as epistemic cognition. Epistemological beliefs were initially ascertained from an administration of the Epistemological Beliefs Assessment for Physical Science (EBAPS). Analyses of various qualitative data afforded the tagging of cases as exhibiting naive or sophisticated epistemology. The paper reiterates that epistemological beliefs contribute to students' metacognitive behaviors. An individual exhibiting naive epistemology resorts to simplistic ways of acquiring knowledge and demonstrates low meta cognitive behaviors. On the other hand, an individual manifesting sophisticated epistemology selects study strategies for understanding, is more engaged in her learning, and overtly demonstrates high metacognitive behaviors.
Keywords: Behaviouralism (Psychology)